การพัฒนาการจัดการอาชีวศึกษาจังหวัดชายแดนภาคใต้ - พวงจันทร์, สุมาวดี; สังข์ทอง, เอกรินทร์; วาณิชย์ศุภวงศ์, ผ่องศรี; ชูสุวรรณ, เรชา (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 26 No 2 (2558): Academic Services Journal, Prince of Songkla University, 2015)
บทความนี้สะท้อนให้เห็นพัฒนาการการจัดการอาชีวศึกษาของเขตพัฒนาพิเศษเฉพาะกิจจังหวัดชายแดนภาคใต้จากอดีตจนถึงปัจจุบัน โดยเฉพาะจุดเริ่มต้น หลักการ ยุทธศาสตร์สำคัญๆ รวมถึงวิสัยทัศน์ พันธกิจ และเป้าหมายที่เกี่ยวกับการจัดการอาชีวศึกษา ประโยชน์ของบทความนี้จะช่วยให้ผู้สนใจและผู้เกี่ยวข้องเข้าใจภาพรวมและจุดเน้นของการจัดการอาชีวศึกษาในบริบทของการเปลี่ยนแปลง การพัฒนาการจัดการอาชีวศึกษาของเขตพัฒนาพิเศษเฉพาะกิจจังหวัดชายแดนภาคใต้ เป็นการจัดการศึกษาเพื่อการพัฒนาอาชีพและการมีงานทำเพื่อแก้ปัญหาความยากจนของผู้คนในพื้นที่ ทั้งนี้การพัฒนาการจัดการอาชีวศึกษาในพื้นที่ดังกล่าวเป็นไปอย่างสอดคล้องกับความเปลี่ยนแปลงบริบททางสังคมและภูมิภาค สถานศึกษาอาชีวศึกษา 18 แห่ง เป็นสถานศึกษาที่มีบทบาทสำคัญในการขับเคลื่อนนโยบายในการพัฒนาการศึกษาจังหวัดชายแดนภาคใต้ โดยนำยุทธศาสตร์พระราชทาน “เข้าใจ เข้าถึง พัฒนา” และ “ปรัชญาเศรษฐกิจพอเพียง” มาใช้ดำเนินงานในพื้นที่ซึ่งอาศัยหลักการบริหารจัดการอาชีวศึกษา 3 รูปแบบ คือ การศึกษาในระบบ การศึกษานอกระบบ และการศึกษาระบบทวิภาคี ด้วยยุทธศาสตร์สำคัญ 4 ประการ คือ 1) ขยายโอกาสการเรียนสายอาชีพ 2) สร้างอาชีพและการมีงานทำให้ประชาชนเพื่อสังคมสันติสุข 3) พัฒนาคุณภาพอาชีวศึกษา และ 4) เพิ่มศักยภาพสถานศึกษาและสร้างความปลอดภัย คำสำคัญ: การจัดการอาชีวศึกษา, จังหวัดชายแดนภาคใต้   This article reflects the management of vocational education development of Special Administrative Development Zone in Southern border provinces from the past until the present, especially its beginning, principles, main strategies as well as visions, missions and goals of vocational education management. This article benefits interested persons and stakeholders to understand the overall picture and focuses of vocational education management in the changing context. The management of vocational education development of Special Administrative Development Zone in Southern border provinces emphasizes on future employment and career development in solving poverty problems in the region. Apparently, the development of vocational education in the region corresponds with changes in social context and locality. The 18 vocational education institutes in Special Administrative Development Zone in Southern border provinces play significant roles in driving policies for vocational education management by bringing the royal guidance strategies “understanding, approaching, and developing” and “sufficiency economy approach” into practice with the principles of formal education, non-formal education and dual vocational training systems in following 4 main strategies of 1) expanding vocational education opportunity, 2) creating people’s career and jobs for peaceful society, 3) developing vocational education quality, and 4) increasing potential of colleges and security. Keywords: vocational educationmanagement, southern border provinces